2013
DOI: 10.1016/j.addr.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Mapping biological behaviors by application of longer-lived positron emitting radionuclides

Abstract: With the technological development of positron emission tomography (PET) and the advent of novel antibody-directed drug delivery systems, longer-lived positron-emitting radionuclides are moving to the forefront to take important roles in tracking the distribution of biotherapeutics such as antibodies, and for monitoring biological processes and responses. Longer half-life radionuclides possess advantages of convenient on-site preparation procedures for both clinical and non-clinical applications. The suitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 102 publications
0
61
0
Order By: Relevance
“…Schwartz et al (5) reported that the plasma-based approach can produce discrepancies of as much as 274 to 162% in individual patients for self RM dose (after 124 I-labeled mAb administration), as compared with PET/CT image-based dosimetry. It has also been reported that 124 I-labeled mAbs tend to release free radionuclides on antibody internalization, resulting in rapid clearance of the radionuclides from the target tissue, leading to reduced tumor contrast (7) and a change in RMPR over time. Unlike 124 I, 89 Zr appears to be a residualizing radiometal potentially circumventing these problems (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Schwartz et al (5) reported that the plasma-based approach can produce discrepancies of as much as 274 to 162% in individual patients for self RM dose (after 124 I-labeled mAb administration), as compared with PET/CT image-based dosimetry. It has also been reported that 124 I-labeled mAbs tend to release free radionuclides on antibody internalization, resulting in rapid clearance of the radionuclides from the target tissue, leading to reduced tumor contrast (7) and a change in RMPR over time. Unlike 124 I, 89 Zr appears to be a residualizing radiometal potentially circumventing these problems (7).…”
mentioning
confidence: 99%
“…It has also been reported that 124 I-labeled mAbs tend to release free radionuclides on antibody internalization, resulting in rapid clearance of the radionuclides from the target tissue, leading to reduced tumor contrast (7) and a change in RMPR over time. Unlike 124 I, 89 Zr appears to be a residualizing radiometal potentially circumventing these problems (7). However, increased radioactivity in bone, as reported in recent studies (8,9) using 89 Zr as a PET tracer, has not been analyzed adequately yet to assess whether or not in vivo metal release or other mechanisms are involved.…”
mentioning
confidence: 99%
“…This property is not general to all radionuclides, and the community now understands that residualizing radionuclides confer better tumor contrast several days postinjection. 206 This point was shown most elegantly in a recent report comparing 76 Br- and 89 Zr-labeled METmAb (onartuzumab), an internalizing antibody to the receptor tyrosine kinase MET. 207 In this study, residualized 89 Zr produced more persistent images of tumors in mice compared to the nonresidualizing radioisotope bromine-76 ( 76 Br).…”
Section: Zr-transferrin: Contemporary Chemistry Enables New Applicamentioning
confidence: 96%
“…Apart from these positron emitting radionuclides, 64 Cu is a promising one which is especially used for antibody-targeted imaging. 38,39 SPECT and PET are more sensitive rather than other modalities such as optical imaging, CT and MRI. SPECT and PET have higher sensitivity and ability to detect in picomolar levels and while they can provide quantitative detection, no tissue penetration limit was detected.…”
Section: Spect and Pet Imaging And Radiotracersmentioning
confidence: 98%